A STUDY ON THE PERCEPTIONS OF USING CHATGPT AS AN AI WRITING ASSISTANT AMONG THIRD-YEAR ENGLISH MAJORS AT DONG A UNIVERSITY - Hoàng Thị Hồng Thương, Hoàng Thị Hồng Thương; Nguyễn Thị Minh Ngọc, Nguyễn Thị Minh Ngọc (Tạp chí Khoa học Đại học Đông Á, 2025)
In the 4.0 era, AI technology continued to develop to support humans. ChatGPT, developed and produced by OpenAI, was launched at the end of 2022 and has become a phenomenon due to the benefits it offers, especially in the process of learning English. This study examined the perceptions of using ChatGPT as an AI writing assistant among third-year English majors at Dong A University. Suggestions were also made to improve the use of ChatGPT as an AI writing assistant for students. The study involved 90 students at Dong A University and employed a quantitative method. A questionnaire was used to determine students' perceptions of the effectiveness and challenges of using ChatGPT, as well as to propose suggestions for its effective use as an AI writing assistant. The results were expected to show that students generally have a positive attitude toward the benefits provided by ChatGPT, although they may still encounter challenges related to its implementation. Additionally, several suggestions were made for more effective use of ChatGPT as an AI writing assistant.